Penerapan Hukum Waris Secara Hibrida dalam Putusan Hakim yang Membatalkan Hibah Wasiat: Studi Putusan Nomor 2665 K/Pdt/2019 - Arief Zulkifli Nst; hasim purba; Henry Sinaga (Jurnal Hukum Lex Generalis, 2026)
A testamentary gift (legaat) is a specific provision within a will involving the bequest of one or more items of a particular type, or the granting of a right of usufruct (vruchtgebruik) over all or part of the estate. In the case at hand, the validity of a testamentary gift made by a Batak Toba testator to the youngest son (siampudan) from his second marriage is challenged by heirs from his first marriage. Legal complexity arises when judges within the general court system-- adjudicating disputes regarding testamentary gifts made by Protestant Christian testators--invalidate such gifts and apply the one-third (1/3) testamentary limit that prevails in the religious court system. Using case, statutory and conceptual approaches, this research finds judicial inconsistency harming legitimaries and identifies teleological-sociological interpretation in situations where applicable law is already clear.